The Oxygen Reduction Reaction at Graphene Modified Electrodes. Issue 1 (5th December 2013) - Randviir, Edward P.; Banks, Craig E.
Abstract The oxygen reduction reaction (ORR) is studied in acidic media utilising various graphene modified carbon electrodes including pristine graphene, Graphene Oxide (GO) and Q‐Graphene which are compared and contrasted against unmodified edge‐ and basal‐ plane pyrolytic graphite electrodes (EPPG and BPPG, respectively). The ORR is found to be highly dependent upon the material's characteristics where a range of activities are observed; in terms of the smallest (least negative) reduction potential, the relative reactivities are ordered as follows: GO>Q‐Graphene>EPPG>BPPG>Pristine graphene. This phenomenon is discussed in terms of two parameters: i) the density of oxygenated species present and their composition; and ii) the density of edge plane‐like sites. Electrochemical analysis reveals that despite the observed variation in peak potentials from the modification with various graphenes, the underlying ORR mechanism in acidic media proceeds via the 2 electron process forming hydrogen peroxide. Insights from this work are highly important as it allows researchers to understand the electrochemistry of graphene in the ORR which has importance in energy generation and where graphene is used per se and also as fuel cell catalyst supports.